Hearing and Health Outcomes: Recognizing and Addressing Hearing Loss in Hospitalized Older Adults - Mormer, Elaine; Cipkala-Gaffin, Janet; Bubb, Kelsi; Neal, Kelly (Seminars in Hearing, 2017)
As age increases, the prevalence of hearing loss significantly increases, reaching up to 89% of those 80 years and older. Hearing loss in older patients is often unrecognized and its consequences are often underappreciated. Hearing loss can interfere with the ability to exchange important health information and to participate in health care decision-making. Hearing loss during hospitalization increases the risk of misdiagnosis. There is a lack of empirical data regarding prevalence and recognition of hearing loss in hospitalized older adults. In this article, we describe a variety of negative outcomes that may result when older inpatients are functioning with unrecognized hearing loss.
Keywords: Hearing loss; inpatients; health care decision-making; unrecognized hearing loss